2016
DOI: 10.7314/apjcp.2016.17.1.183
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Proliferative Activity and Apoptosis Induction of an Ethanolic Extract of Boesenbergia pandurata (Roxb.) Schlecht. against HeLa and Vero Cell Lines

Abstract: Rhizomes of Boesenbergia pandurata (Roxb.) Schlecht have been reported to contain active compounds with anticancer properties. This research was carried out to examine anti-proliferative and apoptotic induction against HeLa and Vero cells-line. Dried powder of B. pandurata rhizomes was extracted by a maceration method using 90% ethanol. Cytotoxic assays to determine IC 50 and anti-proliferative effects were carried out by MTT methods. Observation of apoptosis was achieved with double staining using acridine or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…This finding indicated that FE had high cytotoxic potency towards 4T1 cells according to Prayong, et al (2008). FE was already known to exhibit high cytotoxic potential in various cells, such as MCF-7 breast cancer cells and HeLa cervical cancer cells (Zaeoung, et al, 2005;Listyawati, et al, 2016). Furthermore, flavonoid compound, in the form of isolates and synthesized from fingerroot, such as panduratin A, boesenbergin A, cardamonin, and pinostrobin, are also known to exhibit anticancer activity towards various cancer cell line (Cheah, et al, 2011;Isa, et al;, Jia, et al, 2016Xian, et al, 2012).…”
Section: Discussionmentioning
confidence: 86%
“…This finding indicated that FE had high cytotoxic potency towards 4T1 cells according to Prayong, et al (2008). FE was already known to exhibit high cytotoxic potential in various cells, such as MCF-7 breast cancer cells and HeLa cervical cancer cells (Zaeoung, et al, 2005;Listyawati, et al, 2016). Furthermore, flavonoid compound, in the form of isolates and synthesized from fingerroot, such as panduratin A, boesenbergin A, cardamonin, and pinostrobin, are also known to exhibit anticancer activity towards various cancer cell line (Cheah, et al, 2011;Isa, et al;, Jia, et al, 2016Xian, et al, 2012).…”
Section: Discussionmentioning
confidence: 86%
“…9,10 Panduratin A is a phytochemical compound which is known to have potent anti-proliferation, antioxidation, and anti-in ammation effects. [9][10][11] As many compounds with antioxidant, anti-proliferative, and anti-in ammation properties are proposed for anti-keloid treatment, 12 panduratin A could be a potential treatment in keloid patients.…”
Section: Discussionmentioning
confidence: 99%
“…This results in reduced collagen type 1 deposition, inhibited broblast proliferation, and induction of cell apoptosis. 9,12 PDGF is also a key proin ammatory cytokine that causes keloid formation and is highly expressed in keloid tissue compared to normal tissue. 19 It is responsible for a central signaling pathway in the development of brosis.…”
Section: Panduratin a Reduces Tgf-β1 And Pdgfmentioning
confidence: 99%
“…Previous research mentioned that B. rotunda hexane extract was toxic to liver, lung, and colon cancer cell lines [ 20 ]. Previous studies stated that the ethanol extract of B. rotunda has antiproliferative activity and induces apoptosis in HeLa cervical cancer cells [ 21 ]. The anticancer activity of B. rotunda is predicted because of the presence of their bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%